Community Music Therapy for Strengthening Social Cohesion in Socio-Environmental Conflicts - Salgado-Vasco, Andres; Cardozo-Ruiz, Oscar Ivan (Voices: A World Forum for Music Therapy, 2025)
This study aimed to analyze the impact of a community music therapy process on strengthening social cohesion among members of the Association of Those Affected by the El Quimbo Hydroelectric Project (Asoquimbo). The research was conducted in the municipalities of Hobo and Garzón in the Huila department of Colombia, where the community is engaged in a socio-environmental conflict with the El Quimbo dam. The methodology, grounded in qualitative research with action-research and grounded theory designs, was developed in four stages: reflection-analysis, community engagement, implementation-closure, and results. The music therapy process, conducted between November 2022 and June 2023, focused on integration, participation, empathy, interaction, social relationships, communication, and expression, strengthening the community determinants of“Identity”and “Agreements.”The results suggest that community music therapy contributed to reinforcing social cohesion in this community. Editorial Comment This research study highlights the value of community music therapy to bolster identity and organization to support environmental protection, connecting the dots to an ecological domain that sometimes seems distant in music therapy’s impact potential. It also presents a case for music therapy’s potential for participation and community strengthening, which, from a decolonial perspective, emerges as a solution for the advancement of impoverishing sociopolitical movements focused on isolation and exploitation.